ANALISIS RESEPSI REMAJA PENONTON VIDEO FYP TERHADAP POPULARITAS KONTEN KREATOR UNIK (@binirehan1) “BEGITU SULIT LUPAKAN REHAN” - ririn tutiasri; Ahimsa Adi Wibowo; Jimmy Putra Pradana (Program Studi Ilmu Komunikasi Universitas Mataram, 2023)
Social media is used by the public to gain popularity instantly, with this phenomenon, many content creators are starting to take advantage of this phenomenon to seek popularity. One example of this phenomenon is the TikTok video @binirehan1